Transforming Islamic and Moral Education with Generative AI: A Statistical Systematic Review - Budiyanto Budiyanto; Ali Said Al Matari; Adiyono Adiyono; Fahmy Ferdian Dalimarta (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The integration of artificial intelligence is reshaping global education. This study systematically investigates the role of semi-supervised generative AI in transforming Islamic and moral education. This study aims to systematically investigate the role of semi-supervised generative artificial intelligence (AI) in transforming Islamic and moral education through a PRISMA-guided statistical systematic literature review. The increasingly widespread integration of AI tools such as ChatGPT, Gemini, DeepSeek, Agnes AI, and Cici has reshaped pedagogical practices, yet few studies have quantitatively examined their impact in faith-based education. A key issue addressed is the limited empirical understanding of how semi-supervised learning models mediate between human-guided moral instruction and AI-driven autonomous reasoning. Data were extracted from 38 peer-reviewed publications (2020–2025) across major databases and analyzed using statistical synthesis and meta-analysis. The results indicate a moderate positive effect size (d = 0.56) for generative AI in enhancing student engagement, critical thinking, and ethical reasoning in Islamic learning contexts. Tools such as ChatGPT and Gemini demonstrated the strongest pedagogical outcomes, while Agnes AI and Cici demonstrated unexplored potential. This study concludes that semi-supervised generative AI offers significant opportunities for pedagogical innovation and improved moral reasoning, although ethical supervision and the development of local AI models remain critical for sustainable implementation.